Design of a Planar Ultra Wide Band Antenna Structure using Stepped Contours - Dr. Sunil Kumar Gupta, Mayank Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
When US-FCC has given approval to license free usage of low power short range antenna then only the researchers have starting to explore the Ultra Wide Band (UWB) antenna. The approval date of this usage was 14 February, 2002. A UWB antenna structure of planar geometry is propounded in this paper. Simulation of this structure is carried by Computer Simulation Technology (CST) Microwave Studio - 2016 software tool. In the designing of the proposed structure a rectangular microstrip patch antenna, partial ground plane, stepped contours and microstrip line feed is utilized. In addition to this the substrate used was a FR-4 substance with height of 1.6 millimeter. The dimensions of the structure taken as a whole are 27 х 36 х 1.6 mm3. This structure functions in entire specified frequency range for UWB and beyond up to 11.67 GHz giving the fractional bandwidth of more than 116 %. For the entire said operating frequency range the VSWR is always lees than 2. The essence of this design is its simple and conformal structure. The peak return loss is obtain at 6.84 GHz of about S11= -44 dB. The Peak Gain (IEEE) of about 5.83 dB at 9.5 GHz. The proposed structure can be commonly used for 3.5 GHz and 5.7 GHz which are specified bands for WiMax and WLAN respectively. The other applications for which the structure cam be utilized are ARN (4.55 GHz), ITU-8 (8.8 GHz), XSCS (7.8 GHz), RLS (3.4 GHz), ITS (5.9 GHz), etc.